Development the societal preference-based utility value set for the Patient Health Questionnaire depression scale in Hungary. (1st June 2022) - Balázs, P.; Rencz, F.; Brodszky, V.
Abstract : Introduction: Depression is associated with high impact on health-related quality of life (HRQoL). Health state valuations are used for cost-effectiveness analysis to provide results for health-policy interventions. Objectives: The study aims to estimate a population-based value set of depression described by Patient Health Questionnaire (PHQ-9). We intend to assess vignettes describing PHQ-9 health states to estimate utility values Methods: Current research elicited direct utility scores using time trade-off (TTO) method obtained from the Hungarian general population (N=2, 000). TTO vignettes were created to describe hypothetical health states of depression based on the nine items of PHQ-9. The hypothetical health states were sorted orthogonally in 11 blocks, each containing 4 vignettes (combinations of no; mild; moderate; severe depression). All respondents valued the four health states of one randomly given block. Conventional TTO method was applied, using a 10-year timeframe, while the first iteration step was randomized to 1, 3 and 5 year. Preference weights were estimated using regression model fitted to TTO utility results. Results: Altogether 1, 999 respondents valued overall 34 different health states. The mean age was 47.3 (16.9) years, the majority was female (57.2%). Nearly half of the respondents were secondary educated 45.4%, 27.3% higher educated and 27.2% completed primary school. The mean TTO utility of selected mild, moderate and severe depression was: 0.83; 0.82 and 0.77 respectively. Conclusions: Our results constitute the first population-based value set for PHQ-9. Utility scores give useful information for cost-effectiveness assessments. Estimates provide preference-based quality of life weights for the Hungarian population. Disclosure: No significant relationships.